2013
DOI: 10.1080/00221325.2011.642028
|View full text |Cite
|
Sign up to set email alerts
|

Are Emotion and Mind Understanding Differently Linked to Young Children's Social Adjustment? Relationships Between Behavioral Consequences of Emotions, False Belief, and SCBE

Abstract: According to empirical findings, emotional knowledge and false belief understanding seem to be differently linked to social adjustment. However, whereas false belief is assessed through the capacity to identify its behavioral consequences, emotion tasks usually rely on the comprehension of facial expressions and of the situational causes of emotions. The authors examined if the documented relationship between social adjustment and emotion knowledge in children extends to the understanding of behavioral consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…Children who are good at identifying and understanding other people's positive and negative emotions should interact successfully with them, be socially responsive and develop harmonious relationships in daily life. Moreover, when children are able to infer knowledge, intentions and beliefs and to understand false beliefs, this may help them to adopt other people's cognitive perspective and adjust their own behavior (Deneault and Ricard, 2013;Nader-Grosbois, et al, 2013;Wellman, et al, 2011). Children's abilities to understand emotions play an important role in their concurrent and later academic and social success, (Denham et al, 2012; and social and emotional aspects of preschoolers have recently been considered by researchers as crucial for concurrent and later well-being and mental health.…”
Section: Both Form What Is Known As Cognitive Empathy (Shamay-tsoorymentioning
confidence: 99%
“…Children who are good at identifying and understanding other people's positive and negative emotions should interact successfully with them, be socially responsive and develop harmonious relationships in daily life. Moreover, when children are able to infer knowledge, intentions and beliefs and to understand false beliefs, this may help them to adopt other people's cognitive perspective and adjust their own behavior (Deneault and Ricard, 2013;Nader-Grosbois, et al, 2013;Wellman, et al, 2011). Children's abilities to understand emotions play an important role in their concurrent and later academic and social success, (Denham et al, 2012; and social and emotional aspects of preschoolers have recently been considered by researchers as crucial for concurrent and later well-being and mental health.…”
Section: Both Form What Is Known As Cognitive Empathy (Shamay-tsoorymentioning
confidence: 99%
“…Empirical studies have shown that children who are good at identifying and understanding other people"s emotions interact successfully with them and have good social adjustment (Cutting & Dunn, 1999;Deneault & Ricard, 2013;Nader-Grosbois, Houssa, & Mazzone, 2013). When children are able to take other people"s perspective and to infer and understand others" beliefs, they can adjust their own behavior in social situations.…”
Section: Journal Of Education and Training Studiesmentioning
confidence: 99%
“…According to the ToM model, preschoolers develop the ability to understand their own and other people"s mental states, to take other people"s perspective, and to infer what they know, believe, or feel (Deneault & Ricard, 2013;Denham & Burton, 2003;Denham et al, 2011;Flavell, 1999;Wellman, 1991). Empirical studies have shown that children who are good at identifying and understanding other people"s emotions interact successfully with them and have good social adjustment (Cutting & Dunn, 1999;Deneault & Ricard, 2013;Nader-Grosbois, Houssa, & Mazzone, 2013).…”
Section: Journal Of Education and Training Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we refer to the Theory of Mind (ToM) and the Social Information Processing (SIP) models. ToM conceptions include the capacity to understand one's own and other's mental states, to infer other's mental states and then to adapt one's behavior to others social situations [11] [12]. Some studies have identified deficits in children with EB in the recognition of emotions and the understanding of causes and consequences of emotions [13] [14] [15], difficulties in interpreting other people's behavioral intentions [16], or deficits in the understanding of beliefs [17] [18].…”
Section: Introductionmentioning
confidence: 99%